Blood telegram: India's secret war in East Pakistan - Bass , Gary J author (Gurgaon: Random House, 2013)
"A full-length account of the involvement of Richard Nixon and Henry Kissinger in Pakistan's brutal 1970s military dictatorship argues that they encouraged China's military presence in India, illegally supplied weapons used in massacres and embraced military strategies that have negatively impacted geopolitics for decades. By the author of Freedom's Battle."
Keywords: 9